The Polaire Brotherhood (La Fraternité polaire) in Belgrade - Radulović, Nemanja (Aries, 2023)
The Polaire Brotherhood (La Fraternité polaire) was an occult society active in interwar Paris. Some of the important names of the French occult scene of the period were among its members. According to the reports in the bulletin of the society, there was also a branch operating in Belgrade in the 1930s. However, this has not previously been confirmed. Archive materials used for this paper attest to the existence of the Belgrade group for the first time. Its most important figure was Ksenija Atanasijević (1894–1981), a prominent philosopher. Therefore, attention is also paid to her involvement with Theosophy and co-masonry and the place of esotericism in her work. The activity of the group reminded of the Theosophical—it included meetings, lectures and meditations. They were also familiar with The Oracle of Astral Force (the Fraternité’s key method). The existence of a branch of the French brotherhood in this period can be understood in the context of the French-Serbian cultural relations. This interest in the “alternative” helps us get a better understanding of the history of Serbian intellectuals.